Direct demonstration of termination signals for RNA polymerase II from the sea urchin H2A histone gene. - Briggs, D; Jackson, D; Whitelaw, E; Proudfoot, N (1989)
Previous studies [1,2] suggested but did not prove that the sea urchin H2A histone gene possesses strong transcriptional termination signals close to, but separate from, the 3' processing signals. In this study we have demonstrated by two independent approaches that these sequences elicit authentic transcriptional termination. First we show by nuclear run off analysis that nascent transcription terminates in the immediate 3' flanking region of the H2A gene, in an A-rich region. Second we show that these termination signals prevent transcriptional read through when placed in the intron of a globin gene. The intronic position of the termination signal rules out any effect on steady state mRNA levels. We have therefore defined DNA sequences which act as a transcription terminator when placed in heterologous RNA polymerase II genes.